A Serological Study of Newcastle Disease in Pre- and Post-Vaccinated Village Chickens in North of Iran - Hassanzadeh, M.; Fard, M.H. Bozorgmeri (International Journal of Poultry Science, 2004)
Newcastle disease is one of the major problems for village chicken production, which is an important item in the economy of villages in Iran. In order to investigate the Newcastle disease status in village flocks of Iran, a serological study was performed on the prevalence of Newcastle disease in pre- and post-vaccinated village chickens by means a haemagglutination inhibition (HI) test. In the first experiment, a serological survey was carried out to detect antibodies against Newcastle disease virus in unvaccinated chickens of four villages. In a second study, conventional vaccines, routinely considered for the control of Newcastle disease, were evaluated. Immune responses in unvaccinated chickens indicated a previous exposure of the birds to a natural infection of Newcastle disease virus. No significantly difference was found between the antibody titres of HB1 vaccinated birds and the unvaccinated control birds. However, birds that received an inactivated vaccine, had significantly higher antibody titres compared with the live vaccinated birds. Furthermore, the highest antibody titres were detected in the group of birds that was only given the inactivated vaccine or booster vaccine by veterinary technicians (TI, THI). Our results provide strong evidence for the presence of Newcastle disease virus in village poultry populations of Iran. Due to the high infection potential, vaccination campaigns by inactivated conventional vaccines will have more benefit if they can be applied by the personal who has suitable technical experience.